Pentingnya Safety Culture di Rumah Sakit: Upaya Meminimalkan Adverse Events - Budihardjo, Andreas (Universitas Prasetiya Mulya, 2008)
Adverse Events (AEs), which are also known as the unexpected events, can happen in any hospital, and can cause dangerous impacts on patients’ life. In Indonesia, empirical research on AEs is still limited in number therefore there are a lot of AEs which are not identified and analyzed. In fact, a great number of AEs can be prevented through the implementation of safety culture, safety system and information technology. It is now the time for hospitals and health centres to apply patient-safety culture more effectively. This article discusses the role and essence of patient-safety culture in minimizing the total number of AEs. Hospitals and health centres are encouraged to manage their corporate culture change into the direction of applying the safety culture appropriately in order to provide a positive impact on the patient life and hospitals’ image. Eventually, an integrative model which links the patient safety culture with the hospital performance is provided.